Woman against a Woman? Inherited Discourses to Reproduce Power: A Gender Discourse Analysis of School Textbooks in the Context of Georgia - Shalva Tabatadze (MDPI AG, 2023)
This study conducted a critical discourse analysis of research studies on school textbooks conducted in Georgia. The research aimed to address the following questions: What specific discourses are identified in school textbooks developed under the first, second, and third generations of the National Curriculum in Georgia? What factors contribute to the development of these identified discourses in the context of Georgia's educational system? A total of ten published research studies in this field were selected for analysis. Feminist Critical Discourse Analysis (FCDA), developed by Lazar was used for the categorization of discourses. This discourse analysis yielded significant findings and carried both theoretical and practical implications. First, the study uncovers a noteworthy pattern in school textbooks and contributes to the development of a framework for analyzing school textbooks. Second, the study identified the formation of specific discourses through the omission and invisibility of women. This pattern is termed the development of "language-free" discourses. Third, the study demonstrated that the structural power of women in education alone is insufficient for transforming power relations through discursive practices. Therefore, in order to achieve transformation and change, it is important to challenge and transform the learned and inherited discourses of those who hold power in education. Fourth, the value of this research study is its contribution to identifying future research directions in the field.